Utilisation of Trash Fish I. Preparation of Fish Flake - VENUGOPALAN, V.; GOVINDAN, T. K. (Fishery Technology, 1967)
The paper deals with the investigations carried out on the preparation of odourless fish-starch flakes using partially deodourised trash fish meat and different sources of starch like corn, tapioca, maida and blackgram. It has been found that the products using corn and tapioca are better compared to those -prepared using other two starches, the product from corn being the best. The product has a protein content of about 20% and has been found to have a storage life of 4 months at 37°C.